Effect of volcanic ash as partial replacement of ground-granulated blast-furnace slag based alkaline activated mortar. Issue 1 (1st February 2022) - Karolina, Rahmi; Tarigan, Johannes; Megat Johari, Megat Azmi; Hardjasaputra, Harianto; Mijarsh, M.J.A.
Abstract: Volcanic ash obtained from Mount Sinabung is an aluminosilicate material that is generally available deposited in the land of Sinabung. The study focuses to investigate the effect of volcanic ash as partial replacement of ground-granulated blast-furnace slag (GGBFS) based alkaline activated mortar (AAM) in varying six ratios from 10 wt.% to 60 wt.% in terms of the compressive strength (CS) and structural characteristics. The six-mixture design of AAM was conducted with addition of alkaline activator solution (AAS) to solid material. The AAS were prepared from a combination of 10 M NaOH and Na2 SiO3, whereas, solid materials consisted of GGBFS, VA and fine aggregates. The results of the experiments were analysed by CS at the age of 7, 28, and 56 days and supported by SEM characterization for the optimum mixture. The results have revealed that the least significant factor in terms of compressive strength value is the addition of volcanic ash content whereby the highest value of 93.50 MPa produced by Va 10% and the lowest of 35.80 MPa from Va 60% for all of ages day. In addition, the regression linear values show the overall compressive strength decreased slowly over the ages. Contrastingly, the addition of volcanic ash higher than 40% exhibited an increment of compressive strength. Based on SEM observation dense and continuous microstructure was observed which reflects a high degree of polymerization reactions. At the same time, no cracks were observed in the surface microstructure that shows proper aggregate-binder bonding that influences the compressive strength results finding.